2007
DOI: 10.1177/159101990701300207
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Aneurysm of the Superior Cerebellar Artery

Abstract: Following a head trauma in a 40-year-old male, massive subarachnoid hemorrhage and fractures of the skull base/clivus was found at CT. CT angiography demonstrated an aneurysm on the proximal part of the right superior cerebellar artery. The aneurysm was successfully coiled without any complication and the patient improved clinically during the following three months. The decline in use of angiography in head trauma patients during the last two decades may lead to a lower detection of traumatic aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Not unlike the experience of others we have seen fewer reports of traumatic aneurysms in connection with severe head traumas following the introduction of CT as the primary radiolog- ical tool in head traumas. In the late 70`s and early 80`s when cerebral angiography was still an important tool in diagnosing the nature of damage to the brain, traumatic aneurysm seemed to be more frequently reported 7,8,9,10,11 . In later years reports have been more sporadic 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Not unlike the experience of others we have seen fewer reports of traumatic aneurysms in connection with severe head traumas following the introduction of CT as the primary radiolog- ical tool in head traumas. In the late 70`s and early 80`s when cerebral angiography was still an important tool in diagnosing the nature of damage to the brain, traumatic aneurysm seemed to be more frequently reported 7,8,9,10,11 . In later years reports have been more sporadic 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“… 11 In fact, during the pre-CT era, when angiograms were used as first-line surveys, TAs were diagnosed early. 10 , 16 Currently, noncontrast CT is instead routinely used to screen TBI; thus, TA tends to be overlooked at primary surveys. Our review of the older reports showed that TAs are probably present immediately after injury.…”
Section: Discussionmentioning
confidence: 99%
“… 7 So far, there is a paucity of reports of TA found at the superior cerebellar artery (SCA). 1 , 8 , 10–12 We hereby report a lesson learned from a case of SCA-TA after head injury. We also review the literature and discuss the diagnosis and treatment of this entity.…”
mentioning
confidence: 93%
“…The argument was the lack of educated neuroradiologists in their hospital. The well documented complexity 28 and small numbers of neuroradiological procedures in their own country was not considered [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…Publication of scientific papers: Publishing of scientific papers in international and Norwegian peer review journals has been limited to the two largest institutions in Oslo [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . Scientific publishing in cooperation with international institutions has been limited to these two hospitals as well [16][17] .…”
Section: Hour Service: Only the Two Institutions Inmentioning
confidence: 99%